Implementasi Standar Akuntansi Keuangan EMKM terhadap Laporan Keuangan Persekutuan (Studi Kasus pada CV.Dwipa Nusantara) - Arief Pramudya; Fahrul Rahman; Muhammad Ardiansyah; Siti Rodiah (Pusat Riset dan Inovasi Nasional, 2023)
This research is in accordance with the reality that occurred at CV.Dwipa Nusantara, which is located in Payung Sekaki District, Pekanbaru City, which means that businesses that have been around for about 8 years should have prepared financial reports in accordance with SAK EMKM. This study aims to identify and investigate the obstacles faced by the owner of the partnership in compiling their financial statements according to SAK EMKM. This study used a qualitative approach with the problem study method. The data sources used are primary data and data collection methods by conducting personal interviews with business owners. As a result of research showing that CV. Dwipa Nusantara has not implemented SAK EMKM in compiling its financial statements due to the owner's ignorance of SAK EMKM and the appropriate procedures for preparing financial reports, never following an introduction to SAK EMKM and owner orientation which tends to profit from business.